Comment on Julian Go/1 - Beigel, Maria Fernanda (2016)
This is a comment on the paper “Globalizing Sociology, Turning South. Perspectival Realism and the Southern Standpoint,” which main argument points out that social science’s concerns, categories and theories have been formulated, forged, and enacted of and for AngloEuropean metropoles, but how to overcome this problem of “metrocentrism” remains a dilemma. It discusses the place given to the Latin American traditions in the text, the isolation of the contribution of these authors from the strong Southern traditions in which they are inserted and disclaiming local debate.